Quality of life and reconstructive surgery efforts in severe hand injuries - Alawi, Seyed Arash (Innov Surg Sci, 2018)
INTRODUCTION: Severe hand trauma, leading to extensive skeletal and tissue defects, requires plastic surgical reconstruction of the highest level aiming at maximizing function and aesthetics. The intention of this study was to investigate clinical parameters and resource consumption connected with severe hand injuries, with specific emphasis on a follow-up evaluation of quality of life after the reconstruction process. MATERIALS AND METHODS: In this retrospective study, we evaluated patients with severe hand injuries from 2013 to 2016 who had completed surgical and non-surgical treatment. Measures included total period of therapy (TPT) in days, total duration of operations including anesthesia (TOA), total duration of all operations (TO), and total number of operations (TNO). We also determined total inpatient stay (TIS), total number of clinic presentations with interventions (TNPI), initial hand injury severity score (iHISS), and inpatient proceeds (IPP) in Euros (€). Correlation was assessed between iHISS and TOA, TNO, and TIS. Finally, these patients were reexamined in a follow-up inquiry and the life quality was assessed with the five-level version of the EuroQol five-dimensional (EQ-5D) descriptive system (EQ-5D-5L). RESULTS: We analyzed 12 patients with an average age of 44 years (min. 24 years, max. 75 years). Patients receiving reconstructive surgery experienced median ([Image: see text] ) TPT of 175 days [interquartile range (IQR), 51–499], TOA of 13 h (IQR, 6–37), TO of 9 h (IQR, 4–25), and TNO of 5 (IQR, 3–11). Further, the patients’ median TIS was 22 days (IQR, 9–86), TNPI was 4 (IQR, 2–8), and iHISS was 77 (IQR, 44–162). The median IPP was 14.595 € (IQR, 5.541–33.709 €). IHISS was positively correlated with Pearson’s r for TIS (0.817), TOA (0.857), and TNO (0.871). The EQ-5D-5L index value resulted in a high level of life quality with a median of 0.898 (min. 0.8, max. 1). CONCLUSION: Severe hand injuries are related to high efforts for surgical and functional reconstructions, which result in high quality of life measured with the EQ-5D-5L assessment. However, for a defined collective of patients, myoelectric prosthetic functional replacement should be considered. Further studies are necessary to examine functional outcomes and quality of life after bionic prosthetic replacement. Also, a bionic reconstruction score to define hard criteria for taking an acute treatment decision is necessary.